Burden and Trends of IBD in 5 Asian Countries From 1990 to 2019: A Comparison With the United States and the United Kingdom. Issue 4 (21st July 2022) - Gu, Wan-Jie; Ning, Fei-Long; Jin, Hao-Ran; Zhao, Zhe-Ming; Lyu, Jun; Pei, Jun-Peng; Cao, Shi-Yi; Zeng, Yong-Ji; Abe, Masanobu; Nishiyama, Kazuhiro; Zhang, Chun-Dong
Abstract : BACKGROUND: IBD is becoming a global health challenge, with substantial variations in incidence and death rates between Eastern and Western countries. OBJECTIVE: This study aimed to investigate the burden and trends of IBD in 5 Asian countries, the United States, and the United Kingdom. DESIGN: This was a cross-sectional study. SETTING: Data were obtained from Global Burden of Disease 2019 Study. PATIENTS: Patients with IBD were included. MAIN OUTCOME MEASURES: Incidence, death, and age-standardized rates of IBD were measured. RESULTS: The age-standardized incidence and rates of death from IBD gradually decreased worldwide from 1990 to 2019. The age-standardized incidence rate in the United States decreased from 1990 to 2000 and then increased gradually from 2000 to 2019; the age-standardized incidence rates in the United Kingdom, Mongolia, and China increased gradually from 1990 to 2019, whereas in the Democratic People's Republic of Korea, it decreased from 1990 to 1995 and increased gradually from 1995 to 2019. The age-standardized death rate in the Republic of Korea exhibited a rising trend until 1995, fell significantly up to 2015, and then stabilized from 2015 to 2019. The age-standardized death rate in the United States showed a rising trend until 2007, and then decreased gradually from 2007 to 2019, whereas the rate in the United Kingdom showed a rising trend until 2010 and decreased from 2010 to 2019. The age-standardized death rates in China, Mongolia, the Democratic People's Republic of Korea, and Japan decreased gradually from 1990 to 2019. The age-standardized incidence and death rates in the United States and United Kingdom in recent decades were higher than those in the 5 Asian countries. The peak age-standardized incidence rates in the 7 countries were among people of 20 to 60 years of age. The age-standardized death rates in all 7 countries exhibited rising trends with increasing age, with older individuals, particularly those aged ≥70 years, accounting for the most deaths. LIMITATIONS: Limitations of this study include data from different countries with different quality and accuracy. CONCLUSIONS: There have been large variations in the burdens and trends of IBD between 5 Asian countries, the United States, and the United Kingdom during the past 3 decades. These findings may help policymakers to make better public decisions and allocate appropriate resources. See Video Abstract at http://links.lww.com/DCR/B996 . CARGA Y TENDENCIAS DE LA ENFERMEDAD INFLAMATORIA INTESTINAL EN CINCO PAÍSES ASIÁTICOS DESDE 1990 HASTA 2019: UNA COMPARACIÓN CON LOS ESTADOS UNIDOS Y EL REINO UNIDO: ANTECEDENTES: La enfermedad inflamatoria intestinal se está convirtiendo en un desafío en la salud mundial, con variaciones sustanciales en las tasas de incidencia y mortalidad entre los países orientales y occidentales. OBJETIVO: Investigar la carga y las tendencias de la enfermedad inflamatoria intestinal en cinco países asiáticos, EE. UU. y el Reino Unido. DISEÑO: Estudio transversal. ESCENARIO: Estudio de carga global de morbilidad 2019. PACIENTES: Enfermedad inflamatoria intestinal. PRINCIPALES MEDIDAS DE RESULTADO: Incidencia, muerte y tasas estandarizadas por edad de enfermedad inflamatoria intestinal. RESULTADOS: Las tasas de incidencia y muerte estandarizadas por edad de la enfermedad inflamatoria intestinal disminuyeron gradualmente en todo el mundo desde 1990 hasta 2019. La tasa de incidencia estandarizada por edad en los EE. UU. disminuyó de 1990 a 2000 y luego aumentó gradualmente de 2000 a 2019, las tasas en el Reino Unido, Mongolia y China aumentaron gradualmente de 1990 a 2019, mientras que la tasa en la República Popular Democrática de Corea disminuyó de 1990 a 1995 y aumentó gradualmente de 1990 a 2019. La tasa de mortalidad estandarizada por edad en la República de Corea exhibió un tendencia ascendente hasta 1995, cayó significativamente hasta 2015 y luego se estabilizó de 2015 a 2019. La tasa de mortalidad estandarizada por edad en los EE. UU. mostró una tendencia ascendente hasta 2007 y luego disminuyó gradualmente de 2007 a 2019, mientras que la tasa en el Reino Unido mostró una tendencia ascendente hasta 2010 y disminuyó de 2010 a 2019. Las tasas de mortalidad estandarizadas por edad en China, Mongolia, la República Popular Democrática de Corea y Japón disminuyeron gradualmente de 1990 a 2019. La tasa de incidencia estandarizada por edad y mortalidad en los EE. UU. y el Reino Unido en la última década fueron más altas que las de los cinco países asiáticos. Las tasas máximas de incidencia estandarizadas por edad en los siete países se dieron entre personas de 20 a 60 años. Las tasas de mortalidad estandarizadas por edad en los siete países exhibieron tendencias crecientes con el aumento de la edad, y las personas mayores, en particular las de ≥70 años, representaron la mayoría de las muertes. LIMITACIONES: Datos de diferentes países con diferente calidad y precisión. CONCLUSIONES: Ha habido grandes variaciones en las cargas y tendencias de la enfermedad inflamatoria intestinal entre cinco países asiáticos, EE. UU. y el Reino Unido durante las últimas tres décadas. Estos hallazgos pueden ayudar a los formuladores de políticas a tomar mejores decisiones públicas y asignar los recursos apropiados. Consulte Video Resumen en http://links.lww.com/DCR/B996 . (Traducción— Dr. Francisco M. Abarca-Rendon )